AI for 5G networking- A Bibliometric Analysis - Mahajan, Smita; Wagle, Shivali Amit; Sangve, Sunil M.; Gangadhara, Aryani (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The merging of 5G networking with artificial intelligence (AI) has become a game-changing paradigm, completely overwhelming the landscape of communication systems. A thorough bibliometric analysis is presented in this work to help comprehend the developments, patterns, and significant research areas at the nexus of artificial intelligence (AI) and fifth-generation(5G). Through an extensive assessment of conference papers, patents, and academic literature, this investigation delves into the complex interactions that arise between artificial intelligence and 5G technology. This bibliometric analysis is a valuable tool for scholars, policymakers, and industry experts trying to understand the intricacies of AI-enabled 5G networks, as it offers a broad perspective of the scholarly scene. In this dynamic and quickly developing sector, it provides insights into the current level of knowledge, points out research gaps, and lays-out a plan for future studies.